Pengendalian Kualitas Air Limbah Industri Migas di Pertamina Hulu Mahakam (PHM) CPU Tambora Samarinda - Gusti Firman Noor; Khoirul Huda; Mad Yusup; Diyaa Aaisyah Salmaa Putri Atmaja (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2025)
The research was conducted directly at the Pertamina Hulu Mahakam CPU Tambora Samarinda Company. The problem in this study is how to control the quality of wastewater and what factors affect the quality of wastewater in the PHM CPU Tambora Samarinda area, while the purpose of the study was to determine the control of wastewater quality and determine the factors that affect the quality of wastewater. Wastewater sampling was carried out in bottles for 31 days at 06.00 am and then sent to the laboratory for analysis of oil content in wastewater. The method used is the control map approach and fish bone diagram. The results of the study showed that the quality of wastewater was still within the standard quality limit of 12.5 ppm (still below the maximum standard of 40 ppm) and the dominant factor affecting the quality of wastewater was the equipment factor, namely due to damage to the pump